Vegetative anatomy of some Brazilian Zygopetalinae (Orchidaceae) - Pedroso-de-Moraes, Cristiano; Souza-Leal, Thiago de [UNESP]; Barros, Fabio de; Sajo, Maria das Gracas [UNESP] (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2018)
The anatomy of the vegetative organs of the Brazilian Zygopetalinae are poorly known. In the present paper we analyze the anatomy of roots, stems and leaves of twelve species, many of them of uncertain taxonomic position. We compare our results with those previously described for the same subtribe and some anatomical features, such as the number of velamen, root cortex and mesophyll layers, that can be useful in the systematic analysis of determined taxa, specially Dichaea Lindl., Promenaea Lindl. and Zygopetalum Hook. We also found features that can be interpreted as adaptations to drought, a situation that typically prevails in epiphytic environments where most of the species studied here live.
Keywords: Epidendroideae; Maxillarieae; orchid; vegetative habit